Age of acquisition of emotional words in English as a foreign language: The role of bilingual teaching - Sánchez, María Jesús; Pérez-García, Elisa (Círculo de Lingüística Aplicada a la Comunicación, 2025)
This paper investigates at what age English as a foreign language (EFL) learners acquire frequent and emotional (positive and negative) English words. More specifically, it studies whether having attended bilingual programmes influences the age of acquisition (AoA) of the words. A total of 124 Spanish EFL learners at B1/B2 and C1 levels and with and without bilingual experience rated subjectively the AoA of high-frequency and emotional English words in valence, 20 highly positive and 20 highly negative. According to statistical analyses, all learners had acquired the positive words approximately one year earlier than the negative ones. As for the effect of bilingual instruction, the lower-level students with bilingual experience showed significantly lower AoA for the positive words than the higher-level students without bilingual training. For negative words, they also showed a significantly lower AoA compared to the same level and higher-level students without bilingual experience. Overall, the results reveal that positive frequent and emotional words are learned earlier than negative ones in EFL and that the AoA of the latter is reinforced in bilingual teaching programmes.